Nursing research in Brazil in the context of the COVID-19 pandemic: integrative review (Research, Society and Development, 2022)
Objective: to analyze the scientific production about COVID-19 in the field of nursing in journals in the area in Brazil. Materials and Method: integrative literature review, whose search was guided by the PICOT strategy, as follows: P – Nursing; I – not applicable; C – not applicable; O - COVID-19; T – 2020-2021. The studies were searched in SciELO and VHL. Results: 23 articles available in English and Portuguese, published in national journals, were selected. As for the year, 11 were published in 2020 and 12 in 2021. They were divided into three categories: (1) nursing care (n=11); (2) nursing work process (n=9); and (3) technology for nursing care at COVID-19 (n=3), regarding the study design, it was found that most were experience reports (56%) followed by a methodological study (17%). Conclusion: professionals seek to base care practice on scientific evidence and, thus, several study categories were found, both original articles and reflection, experience reports and reviews, which contribute to the discussion and construction of the nursing knowledge about COVID-19.